2002
DOI: 10.1118/1.1477234
|View full text |Cite
|
Sign up to set email alerts
|

A performance comparison of flat‐panel imager‐based MV and kV cone‐beam CT

Abstract: The use of cone-beam computed tomography (CBCT) has been proposed for guiding the delivery of radiation therapy, and investigators have examined the use of both kilovoltage (kV) and megavoltage (MV) x-ray beams in the development of such CBCT systems. In this paper, the inherent contrast and signal-to-noise ratio (SNR) performance for a variety of existing and hypothetical detectors for CBCT are investigated analytically as a function of imaging dose and object size. Theoretical predictions are compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
122
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 23 publications
(28 reference statements)
0
122
0
1
Order By: Relevance
“…Modern C-arm CT systems presently find rapid acceptance since they offer improved image quality, versatility and dedicated applications for planning, guiding, monitoring and assessing interventional procedures [5][6][7][8][9][10][11][12]. These are above all their use in interventional procedures and in intra-operative imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Modern C-arm CT systems presently find rapid acceptance since they offer improved image quality, versatility and dedicated applications for planning, guiding, monitoring and assessing interventional procedures [5][6][7][8][9][10][11][12]. These are above all their use in interventional procedures and in intra-operative imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation dose for a CBCT scan is about 2‐4 cGy and the cumulative dose for a treatment consisting of 30 fractions is about 60‐120 cGy. For a 4D CBCT scan, three or four thousand CB projections are necessary, and the total dose would be more than 10 cGy per scan 3 , 4 , 5 . Therefore, the use of CBCT was precautious in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Groh et al have reported the use of 32 cGy to delineate ~4% density differences. 8 Also, Morin et al have reported using 14.4 cGy to obtain pelvic images with visible soft tissues (e.g., prostate, rectum, fat, and muscle) 22 , and 9 MU to obtain pelvic images having sufficient soft tissue information to guide 3D positioning 23 . If the x-ray detector quantum efficiency could be greatly improved, it is reasonable to expect that soft tissues could be visualized at considerably lower, clinically acceptable doses using megavoltage cone-beam (or fan-beam) CT. For this reason, high efficiency x-ray detectors have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] One such technique that has been clinically implemented involves acquiring cone-beam computed tomography (CBCT) images with a kilovoltage (kV) x-ray source and a diagnostic active matrix flat-panel imager (AMFPI), both orthogonally mounted to the treatment gantry. [5][6][7][8][9][10][11] This system can produce useful CT images at clinically acceptable doses (i.e., a few cGy, which is approximately equal to the dose for one portal image). [8][9][10] Another CT imaging technique that is also under investigation for soft tissue visualization involves the use of the megavoltage (MV) therapy beam and an electronic portal imaging device (EPID).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation